Strategi peningkatan pendapatan petani padi di Kecamatan Gunung Tujuh Kabupaten Kerinci - Seplida, Utari; Tan, Syamsurijal; Yulmardi , Yulmardi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to: (1) determine the socio-economic characteristics of rice farmers in Gunung Tujuh District, Kerinci Regency (2) to determine what factors affect the income of rice farmers in Gunung Tujuh Subdistrict, Kerinci Regency (3) to determine strategies for increasing income rice farmers in Gunung Tujuh District, Kerinci Regency. The quantitative analysis used in this research is regression analysis. Based on the results of multiple regressions, working capital variables, land area, and total production have positive and significant coefficients on farmers' income, where the amount of production variable is the variable that has the greatest influence on the income of rice farmers in Gunung Tujuh District, Kerinci Regency. The results of this study in the form of a strategy to increase rice farmers' income based on internal and external results showed that the main strategy is the strategic focus that must be done, namely optimizing weaknesses and overcoming various threats by reducing land conversion by providing capital, reactivating Gapoktan, optimizing fertilizer use, overcoming the problem of increasing input prices to increase cooperation between extension workers and Gapoktan in Gunung Tujuh District, Kerinci Regency.